Suprapubic grasper–assisted transvesical endoscopic ureterocele puncture: a novel technical innovation. Issue 3 (May 2019) - Gupta, V.; Usman, J.; Mohammed, D.A.; AlMarzouqi, M.
Summary: Although endoscopic drainage remains treatment of choice for ureterocele in pediatric age group, often urologists, especially during the learning phase and difficult anatomy, feel a limitation because of inability to do intravesical manipulation. This can be attributed to absence of the second working channel in pediatric cystoscope owing to size limitation. Herein, we describe a novel technique for safe introduction of a grasper which acts as a second surgical arm for endoscopists and simultaneously facilitates both intravesical manipulation and drainage of ureterocele at an optimal location with minimal complications.